Measuring learning styles in mathematics: A validity and reliability study - Rino Richardo; Robiatul Adawiya; Esthi Nawangsasi; Martalia Ardiyaningrum Ardiyaningrum; Abdus Solihin (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Learning style is one of the factors that can facilitate students in understanding subject matter, especially mathematics. Learning style is related to how students absorb and process mathematical concepts optimally. This has a direct impact on improving student learning outcomes. Therefore, teachers need to design learning activities that are in line with students' learning style tendencies. Thus, a valid and reliable learning style scale instrument is needed.Aims: This study aims to develop a valid and reliable measurement scale instrument to identify the learning style of junior high school students in learning mathematics.Method: This research is measurement scale development research. The respondents of this study totalled 184 students. The content validity test used the Aiken V index formula, while the construct validity used factor analysis. Reliability test used Cronbach alpha testResult: The results of this study indicate that: (1) the developed instrument meets the validity criteria based on Aiken's V analysis and factor analysis; and (2) the instrument also meets the reliability criteria based on the results of Cronbach's alpha analysis. The instrument consists of 6 statements to measure visual learning style, 5 statements for auditory, and 7 statements for kinesthetic.Conclusion: learning style scale has met the criteria of valid and reliable with three factors namely visual, auditory and kinesthetic. These findings can be used by teachers to diagnose students' learning style tendencies as a basis for designing mathematics learning, as well as developing similar scales in different subject contexts.